Gut Microbiota and Tryptophan Metabolism as Therapeutic Targets for Spinal Cord Injury: Insights From Probiotic Treatment - Dong J; Xu C; Jin S; Xie T; Xu Z; Hao D; Dong L (Journal of Inflammation Research, 2025)
Jinwang Dong,1,2,* Chen Xu,1,* Shanshan Jin,3,* Tao Xie,1,* Zhengwei Xu,1 Dingjun Hao,1 Liang Dong1 1Department of Spine Surgery, Honghui Hospital, Xi’an Jiaotong University, Xi’an, Shaanxi, People’s Republic of China; 2School of Medicine, Yan’an University, Yan’an, Shaanxi, People’s Republic of China; 3Department of Rehabilitation, The second People’s Hospital of Cao County of Shandong Province, Heze, Shandong, People’s Republic of China*These authors contributed equally to this workCorrespondence: Liang Dong, Email dongliang-526@163.comBackground: Probiotics have been demonstrated to repair spinal cord injuries (SCI) by improving gut microbiota dysbiosis; however, the specific mechanisms underlying their therapeutic effects on SCI remain incompletely elucidated.Objective: This study aims to investigate the therapeutic effects of probiotics and analyze the mechanisms of probiotic treatment for SCI through the gut-spinal cord axis.Methods: A rat model of SCI was established to evaluate the therapeutic effects of probiotics. Fecal samples were analyzed to assess gut microbiota composition and metabolite profiles, while differential gene expression in spinal cord tissue was examined.Results: Pathological assessments demonstrated that probiotic treatment facilitated structural restoration of the spinal cord tissue. Behavioral evaluations via the Basso Mouse Scale (BMS) and inclined plane tests revealed significant improvements in locomotor recovery after SCI. Metagenomic sequencing showed that probiotics enhanced gut microbiota diversity, particularly enriching the relative abundance of Bacillota (formerly Firmicutes) and Clostridia. Metabolite profiling identified an enrichment of key tryptophan metabolites, including 3-Indoleacetonitrile, Xanthoxic acid, Serotonin, and Tryptophanol. Transcriptomic analysis identified 468 upregulated and 173 downregulated genes in spinal cord tissues. Furthermore, gut microbiota, microbial metabolites and spinal cord gene expression were integrated to construct a “gut microbiota-tryptophan metabolites-signaling pathway network” using Cytoscape v.3.10.2. This network linked 19 microbial species (17 belonging to Bacillota and Clostridia, including seven Lactobacillus species) with tryptophan metabolites and downstream signaling pathways. Among these, tryptophan metabolites activated 17 genes predominantly involved in anti-inflammatory and neuroregenerative processes. Protein-level validation confirmed the neuroprotective and anti-inflammatory effects of probiotics.Conclusion: The “Gut microbiota-tryptophan metabolites-signaling pathway network” offers novel therapeutic targets for SCI injury treatment. Probiotics exert their effects by modulating gut microbiota and enhancing tryptophan metabolism, thereby influencing multiple signaling pathways in the spinal cord that can lead to anti-inflammatory and neuroprotective outcomes. Keywords: Probiotic, Gut-Spinal Cord Axis, Spinal Cord Injury, tryptophan metabolism, Inflammatory Response, Neural Regeneration